Bacteriophage Therapy as an Application for Bacterial Infection in China - Shuang Liang; Yanling Qi; Huabo Yu; Wuwen Sun; Sayed Haidar Abbas Raza; Nada Alkhorayef; Samia S. Alkhalil; Essam Eldin Abdelhady Salama; Lei Zhang (Antibiotics, 2023)
Antibiotic resistance has emerged as a significant issue to be resolved around the world. Bacteriophage (phage), in contrast to antibiotics, can only kill the target bacteria with no adverse effect on the normal bacterial flora. In this review, we described the biological characteristics of phage, and summarized the phage application in China, including in mammals, ovipara, aquatilia, and human clinical treatment. The data showed that phage had a good therapeutic effect on drug-resistant bacteria in veterinary fields, as well as in the clinical treatment of humans. However, we need to take more consideration of the narrow lysis spectrum, the immune response, the issues of storage, and the pharmacokinetics of phages. Due to the particularity of bacteriophage as a bacterial virus, there is no unified standard or regulation for the use of bacteriophage in the world at present, which hinders the application of bacteriophage as a substitute for antibiotic biological products. We aimed to highlight the rapidly advancing field of phage therapy as well as the challenges that China faces in reducing its reliance on antibiotics.